Water balance and crops in Karnataka - SUBRAMANIAM, A. R.; RAO, A. V. R. KESAVA (MAUSAM, 1984)
Karnataka with a spectrum of moist climates offers scope fro a wide variety of crops to be grown. Following Thornthwaite, climatic water balance elements and indices have been calculated for all the available meteorological stations in the State and they are cartographically analysed. The general distribution of crops and the results of the analysis of moisture adequacy are compared to identify the limits of moisture adequacy for certain important crops like rice, jowar, bajra, ragi, sugarcane, groundnut, cotto and coffee. In kharif season, jowar yields are generally found to be recording high production in areas of 70% moisture adequacy.